2019
DOI: 10.1111/jnu.12473
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of Postnatal Care Services Utilization Among Women in Nigeria: A Facility‐Based Study

Abstract: Purpose Adequate utilization of postnatal care (PNC) services is a major contributing factor to reducing maternal mortality among women. Hence, this study was designed to assess the level of utilization of PNC services and its predictors among postpartum women in Ekiti State, Nigeria. Design The study adopted a cross‐sectional descriptive design. Methods A total of 405 postpartum women from primary healthcare centers in five selected local government areas in Ekiti State participated in this study. A self‐stru… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 16 publications
3
12
0
Order By: Relevance
“…Our study shows that lack of financial means is an important barrier in the realization of PNC. Studies confirmed that women living in wealthier households achieve more PNC than those living in poorer households [14] [16] [17] [18] [19] [20]. In Guinea, Demographic Health Survey showed that the percentage of women receiving timely postpartum care increased from 30% in the lowest quintile to 70% in the highest quintile [2].…”
Section: Discussionmentioning
confidence: 99%
“…Our study shows that lack of financial means is an important barrier in the realization of PNC. Studies confirmed that women living in wealthier households achieve more PNC than those living in poorer households [14] [16] [17] [18] [19] [20]. In Guinea, Demographic Health Survey showed that the percentage of women receiving timely postpartum care increased from 30% in the lowest quintile to 70% in the highest quintile [2].…”
Section: Discussionmentioning
confidence: 99%
“…An interviewer-administered standardized structured questionnaire was developed and used after reviewing other similar studies [6,10,[29][30][31][32][33][34]. The questionnaire has consisted of a range of variables; sociodemographic and cultural, socio-economic, and knowledge, attitudes, and health system-related characteristics.…”
Section: Data Collection Tools and Proceduresmentioning
confidence: 99%
“…2 Despite the importance of providing quality health care services by skilled health care professionals during and immediately after childbirth to mothers and infants, the postnatal periods are usually neglected by most mothers due to sociocultural factors associated with new-borns. [3][4][5] Meanwhile, studies have shown that mothers who attend health facilities during postnatal periods where skilled health professionals can identify, observe and manage any health challenge that may arise in the lives of the mothers and their newborn babies [6][7] stand a chance of preventing the occurrence of body and mental damage, 8 as well as child morbidity and mortality than those who did not. 9 Although there has been incredible progress in the global under-five mortality rate which had reduced from 93 deaths (in 1990) and 76 deaths (in 2000) to 39 deaths per 1,000 live births in 201810, the reduction in this rate is uneven across regions and income levels in the world.…”
Section: Introductionmentioning
confidence: 99%